THE RELATIONSHIP BETWEEN IMMUNIZATION STATUS AND MATERNAL KNOWLEDGE ABOUT COMPLEMENTARY FEEDING WITH NUTRITIONAL STATUS IN TODDLER-AGED - Parulian, Tina Shinta; Wuryanti, Euis; Saptiningsih, Monica (Prodi Ilmu Keperawatan, Fakultas Ilmu Kesehatan, UIN Syarif Hidayatullah Jakarta, 2025)
This research was conducted because there is still a high number of patients diagnosed with malnutrition at the Kuningan Private Hospital in 2022 and the results of interviews with mothers mostly answered incorrectly when asked about complementary feeding and most children had not received complete basic immunization. The research aimed to identify the relationship between immunization status and maternal knowledge about complementary feeding with the nutritional status of toddlers at the Kuningan Private Hospital. Quantitative research method with associative design through a cross sectional approach. The total sample was 120 respondents and used purposive sampling technique. Data collection is by measuring the child's weight, height and completion questionnaires with the mother. Univariate analysis used descriptive analysis for immunization status and nutritional status, while for level of knowledge uses central tendency. Bivariate analysis used Spearman Rank. The results of univariate analysis showed that most children received complete immunization and had normal nutritional status and the average knowledge of mothers was 9.7. The results of the bivariate analysis were p value=0.825 for the relationship between immunization status and nutritional status and p value=0.012 for the relationship between maternal knowledge and nutritional status. The conclusion is that there is a relationship between mothers' knowledge about complementary feeding and the nutritional status of toddlers, so it is recommended that mothers increase their knowledge about complementary feeding and hospitals can facilitate this, such as creating online information media or creating WhatsApp groups for mothers to share information with each other and monitor the child's condition.